Customer Analysis Review, Product Quality and Promotion on Purchasing Decisions for Cosmetic Products in E- commerce Shopee - Serin Anasya; Siska Fidia Lestari; Ramlah Puji Astuti (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to determine the influence of customer reviews, product quality and promotions on purchasing decisions for cosmetic products on Shopee e-commerce. The population used in this research is Shopee consumers who have purchased cosmetic products. The sample selection technique in this study used non-probability sampling with the purposive sampling method. This research uses Naresh K Malhotra's theoretical formula with a total of 88 respondents. The analytical methods used include validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis and hypothesis tests (F test and T test). Analysis of the data used can see that the independent variable has an influence on the dependent variable. The research results show that customer reviews (X1) have a significant positive effect on purchasing decisions, product quality (X2) have a significant positive effect on purchasing decisions, and promotions (X3) have a significant positive effect on purchasing decisions. Customer reviews, product quality and promotions simultaneously influence decisions to purchase cosmetic products on Shopee e-commerce.